2014
DOI: 10.1021/np400781y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Fluorometric Microplate Antiadhesion Assay Using Uropathogenic Escherichia coli and Human Uroepithelial Cells

Abstract: A fluorometric microplate assay has been developed to determine Escherichia (E.) coli adhesion to uroepithelial cells (UEC). P-fimbriated E. coli were labeled with BacLight Green and preincubated 30 min with human urine or standard. Fluorescent-E. coli were added to UEC in mircoplates at a 400:1 ratio, incubated 1 h, and washed, and the fluorescence intensity was measured. Specific labeling and adherence were confirmed by flow cytometry. A myricetin (1) standard curve (0-30 μg/mL) was developed; the lower limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
(76 reference statements)
2
27
0
Order By: Relevance
“…Previous studies have shown that cranberry polyphenolic compounds such as proanthocyanidins, 13,14 flavonols and their glycosides (e.g. myricetin, quercetin), 15,16 condensed tannins (e.g. procyanidins, prodelphinidin), 15,17 and phenolic acids (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that cranberry polyphenolic compounds such as proanthocyanidins, 13,14 flavonols and their glycosides (e.g. myricetin, quercetin), 15,16 condensed tannins (e.g. procyanidins, prodelphinidin), 15,17 and phenolic acids (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…myricetin, quercetin), 15,16 condensed tannins (e.g. procyanidins, prodelphinidin), 15,17 and phenolic acids (e.g. benzoic acid) 18 were able to inhibit the in vitro adherence of P-type E. coli to the glycoprotein receptor on epithelial cells or red blood cell analogues.…”
Section: Introductionmentioning
confidence: 99%
“…, ; Kimble et al . ). This method requires extemporaneous labelling before each assay and can lead to batch‐to‐batch variations in fluorescence intensity.…”
Section: Discussionmentioning
confidence: 97%
“…In some of them, the co‐incubation of bacteria and cells was performed in suspension (Kimble et al . ) or a centrifugation step was used to enhance the contact of bacteria with the cells monolayer (Scharenberg et al . ; Rafsanjany et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation